Structural study and large magnetocaloric entropy change at room temperature of La1−x□xMnO3 compounds. Issue 14 (26th February 2020) - Henchiri, C.; Mnasri, T.; Benali, A.; Hamdi, R.; Dhahri, E.; Valente, M. A.; Costa, B. F. O.
Abstract : In this study, our central focus is to investigate the magnetocaloric characteristics of a La1− x □ x MnO3 ( x = 0.1, 0.2 and 0.3) series prepared by a sol–gel technique. Abstract : In this study, our central focus is to investigate the magnetocaloric characteristics of a La1− x □ x MnO3 ( x = 0.1, 0.2 and 0.3) series prepared by a sol–gel technique published in Prog. Mater. Sci., 93, 2018, 112–232. The crystallographic study revealed that our compounds crystallize in a rhombohedral structure with R 3̄ c . Ferromagnetic (FM) and paramagnetic (PM) characters were detected from the variation in magnetization as a function of magnetic fields at different temperatures. The second order transition was verified from the Arrott plots ( M 2 vs. ( μ 0 H / M )), where the slopes have a positive value. In order to verify the second order, we traced the variation of magnetization vs. temperature at different magnetic fields for x = 0.2. This revealed a ferromagnetic (FM)–paramagnetic (PM) transition when temperature increases. Relying on the indirect method while using the Maxwell formula, we determined the variation in the entropy (−Δ S M ) as a function of temperature for different magnetic fields for the three samples. We note that all the studied systems stand as good candidates for magnetic refrigeration with relative cooling power (RCP) values of around 131.4, 83.38 and 57.26 J kg −1 with magnetic fields below 2 T, respectively. Subsequently, the magnetocaloric effect was investigated by a phenomenological model for x = 0.2. The extracted data confirm that this phenomenological model is appropriate for the prediction of magnetocaloric properties. The study also demonstrated that this La0.8 □0.2 MnO3 system exhibits a universal behaviour.